Acute effects of nonexcitatory electrical stimulation during systole in isolated cardiac myocytes and perfused heart. Issue 8 (5th August 2014) - Blinova, Ksenia; Stohlman, Jayna; Krauthamer, Victor; Knapton, Alan; Bloomquist, Erik; Gray, Richard A.
Abstract Application of electrical field to the heart during the refractory period of the beat has been shown to increase the force of contraction both in animal models and in heart failure patients (cardiac contractility modulation, or CCM). A direct increase in intracellular calcium during CCM has been suggested to be the mechanism behind the positive inotropic effect of CCM. We studied the effect of CCM on isolated rabbit cardiomyocytes and perfused whole rat hearts. The effect of CCM was observed in single cells via fluorescent measurements of intracellular calcium concentration ([Ca2+]i) and cell length (L). Cells were paced once per second throughout these recordings, and CCM stimulation was delivered via biphasic electric fields of 20 ms duration applied during the refractory period. CCM increased the peak amplitude of both [Ca2+]i and L for the first beat during CCM compared to control, but then [Ca2+]i and L decayed to levels lower than the control. During CCM, all contractions had a faster time to peak for both [Ca2+]i and L; after stopping CCM the rise times returned to control levels. In the whole rat heart, the positive inotropic effect of CCM stimulation on left ventricular pressure was completely abolished in the presence of metoprolol, a beta‐1 adrenergic blocker. In summary, the CCM‐induced changes in intracellular calcium handling by cardiomyocytes did not explain the sustained positive inotropic effect in the whole heart and the β‐adrenergic pathway may be involved in the CCM mechanism of action.